2017
DOI: 10.1021/acssynbio.7b00106
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Pro–Asp Sequences Exposed on Bacteriophage M13 as an Ideal Anchor for Gold Nanocubes

Abstract: Bacteriophages are thought to be ideal vehicles for linking antibodies to nanoparticles. Here, we define the sequence of peptides exposed as a fusion protein on M13 bacteriophages to yield optimal binding of gold nanocubes and efficient bacteriophage amplification. We generated five helper bacteriophage libraries using AE(X)DP, AE(X)DP, AE(X)DP, AE(X)DP, and AE(X)DP as the exposed portion of pVIII, in which X was a randomized amino acid residue encoded by the nucleotide sequence NNK. Efficient phage amplificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…An asparagine-toarginine mutation at position 381 of the M13 pVII protein allowed the phage to recognize and bind carbon nanotubes selectively, thus scaffolding the tubes into three-dimensional structures (120). Finally, M13 has been engineered to template gold nanoparticles, as well as nanoparticles made of other metals, illustrating its versatility in the creation of novel bionanomaterials (121,122).…”
Section: Phage-based Nanomaterialsmentioning
confidence: 99%
“…An asparagine-toarginine mutation at position 381 of the M13 pVII protein allowed the phage to recognize and bind carbon nanotubes selectively, thus scaffolding the tubes into three-dimensional structures (120). Finally, M13 has been engineered to template gold nanoparticles, as well as nanoparticles made of other metals, illustrating its versatility in the creation of novel bionanomaterials (121,122).…”
Section: Phage-based Nanomaterialsmentioning
confidence: 99%
“…With the aid of the binding motif, plasmonic nanoparticles could bind to even larger peptide-based scaffolds such as proteins, DNA, and viruses. 68–78 For example, bacteriophages with the exposed Val–Ser–Gly–Ser–Ser–Pro–Asp–Ser (VSGSSPDS) N-terminal sequence have been applied in the formation of gold nanoarchitectures based on its reactivity to gold surfaces. 74,79 Recently, Lee and coworkers showed that peptides with the Pro–Asp (PD) sequence could provide strong binding of gold nanocubes.…”
Section: Chiral Morphologymentioning
confidence: 99%
“…74,79 Recently, Lee and coworkers showed that peptides with the Pro–Asp (PD) sequence could provide strong binding of gold nanocubes. 73 A series of bacteriophage libraries with randomized exposed N-terminal amino acid motifs were found by experiment to have an optimal binding affinity for gold nanoparticles and efficient bacteriophage amplification. The Pro–Asp sequence exhibited amplification yields and the optimal binding of gold nanocubes, suggesting that the Pro–Asp sequence possesses or can increase the affinity for gold nanoparticles.…”
Section: Chiral Morphologymentioning
confidence: 99%